On some general distributions in terms of generalized functions (1978)
In this paper, a general distribution derived from a generalized Bessel function, together with a generalized Beta distribution are discussed. An alternate method for obtaining the distribution of the sum of n independent random variables for the first distribution is obtained. Three of the parameters in this distribution are estimated by different methods under certain conditions. Distribution of maxima and mínima are also considered. For the generalized Beta distribution, esti mates are put in closed form in terms of the generalized hypergeometric function FA.